2018
DOI: 10.1038/s41419-018-0875-4
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ated PXR is a critical regulator of acetaminophen-induced hepatotoxicity

Abstract: Acetaminophen (APAP) overdose is the most frequent cause of acute liver failure and remains a critical problem in medicine. PARP1-dependent poly(ADPribosyl)ation is a key mediator of cellular stress responses and functions in multiple physiological and pathological processes. However, whether it is involved in the process of APAP metabolism remains elusive. In this study, we find that PARP1 is activated in mouse livers after APAP overdose. Pharmacological or genetic manipulations of PARP1 are sufficient to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Acetaminophen is a widely used drug to relieve pain and reduced fever however its higher doses could led to acute liver failure and critical health problems (13). Many studies also reported that it induces the apoptosis and inhibits cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen is a widely used drug to relieve pain and reduced fever however its higher doses could led to acute liver failure and critical health problems (13). Many studies also reported that it induces the apoptosis and inhibits cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Co-Immunoprecipitation: Co-IP assay was performed as previously reported, [36,37] with antibodies specific for Myc (Cell Signaling Technology, 2276), Flag (Cell Signaling Technology; 14793). The bead bound proteins were released and analyzed by Western blot.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed to detect the related protein levels [19,20]. Tissues or cells were homogenized, boiled, separated by SDS-PAGE electrophoresis and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%